The scenes of nostalgia in the poems of Amryalqys - Ibrahimi, Izzet Mulla; Nejad, Sadeq Jafari (Journal of Humanities & Social Sciences, 2017)
Nostalgia in the Arabic is equivalent of "Alhnyn to Al-Mady" and despite that recently entering into many different areas of science is not new by any means, also can be found in the Jaheli (ignorant) literature in abundance so that the Jaheli (ignorant) poet returns to the past and calls his earlier memories. And what that brings him to readout the memories and nostalgia craze is his roam and unhappy present. Sadness, fatigue, pain and suffering those human sustains, generally human, and especially poet gets the sense of nostalgia. So nostalgia is a grief that happens in the result of being away from home and fatherland and according to another definition it is a kind of a desire that is mingled with regret to the past. This phenomenon is emerged in the result of environmental, social, political and psychological factors of Jaheli (ignorant) society in the poem of Jaheli (ignorant) poet and especially in cry poem on Atlal and Deman. One of the most famous poets of the Jaheli (ignorant) who takes delight for the past in his poems is Amryalqys, the leader of Arab poetry. Who was moaning due to lost the kingdom, home and being away from his mistress. Suggests that many factors led to that he comes back to his happiness past until he found that period remedy to his chagrin. One of the factors that returns him to nice dream and unrepeatable days of the past is his too much emotion. This study tries to show the reality of nostalgia in the poems of Amryalqys using a descriptive- Analytical method and study the reasons and types of that.